An eighth-mode SIW antenna for Low-Power Wide-Area Network applications. Issue 13 (2nd September 2021) - Muntoni, Giacomo; Casula, Giovanni Andrea; Montisci, Giorgio; Pisanu, Tonino; Rogier, Hendrik; Michel, Andrea
Abstract : A wearable textile antenna based on the fundamental mode of an eighth-mode substrate-integrated waveguide cavity is presented for Low-Power Wide-Area Network (LPWAN) applications. The antenna operates in the UHF frequency band, at 867 MHz, and exhibits compact size, minimal manufacturing complexity and very low production cost. High isolation from the human body is observed, and a planar size reduction by more than 50% is achieved compared to similar SIW antennas in the literature. The proposed wearable antenna has been designed using CST Microwave Studio, then manufactured and tested, showing very good agreement with predicted performance.